The family experience: a reader in cultural diversity - Hutter, Mark ed. (New York: Macmillan, 1991)
Contents : Multicultural perspectives,the changing family : origins,history and politics,inevitabilities of prejudice,the family and modern society,the family in the community,immigrant families,social policy and poverty families,dating and courtship,sexuality and intimacy,power and intimacy,family and workplace organization,patterns of parenthood,childhood and adolescence.
Includes bibliographical references and index
Keywords: Familia - Sociología Familiar